Pengaruh Biaya Produksi, Biaya Promosi Dan Volume Penjualan Terhadap Laba Pada PT. Unilever Tbk Periode 2017-2021 - Dea Ratna Puspita; Fazhar Sumantri; Mu’mina Mu’mina; Maulidia Hilmiar; Ivontiana Nganus; Maya Anggraeni; Dhelvia Devitha Shalihah (Peneliti.net, 2022)
In this digital era, most companies are already using advanced technology in all things, including in producing goods that already use machines and promoting goods through the internet. This research is used to analyze the effect of production costs, promotions and sales volume on profits. This study uses quantitative research methods, using company secondary data by taking financial data at the company PT Unilever Tbk through the official website. In this study, it is explained how much influence the production costs, promotion costs and sales volume will have on the profit to be achieved. There is an f test which shows that the variables of production costs, promotion costs and sales volume have a significant effect on profit. The results of the research that the variables of production, promotion, and sales volume have a joint effect of 89.2% on the company's profit variable and the remaining 10.8% are influenced by other variables outside of this study.